2019
DOI: 10.1002/jcla.22992
|View full text |Cite
|
Sign up to set email alerts
|

Association between the TOX3 rs3803662 C>T polymorphism and recurrent miscarriage in a southern Chinese population

Abstract: Background Studies have shown that some genetic polymorphisms associated with breast cancer susceptibility may also be associated with abortion. The TOX3 gene plays a key role during the onset of breast cancer, and reproductive factors such as abortion are risk factors for breast cancer. However, there is currently no study describing the relationship between the TOX3 rs3803662 C>T polymorphism and the risk of recurrent miscarriage. Therefore, we investigated whether the TOX3 rs3803662 C>T polymorphism is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The researchers supposed that TOX3 mutation is related to RM. Similar to the genetic polymorphism of LncRNA CCAT2, which is related to both breast cancer and RM (Che, Huang, et al, 2019a), but they did not find any significant correlation with TOX3 rs3803662 polymorphism and repeated miscarriages(W. Huang, Zhou, Li, et al, 2019).…”
Section: Genetic Susceptibility To Recurrent Miscarriagementioning
confidence: 88%
“…The researchers supposed that TOX3 mutation is related to RM. Similar to the genetic polymorphism of LncRNA CCAT2, which is related to both breast cancer and RM (Che, Huang, et al, 2019a), but they did not find any significant correlation with TOX3 rs3803662 polymorphism and repeated miscarriages(W. Huang, Zhou, Li, et al, 2019).…”
Section: Genetic Susceptibility To Recurrent Miscarriagementioning
confidence: 88%
“…Shi et al recently published a large meta‐analysis in which 53 polymorphisms of 37 genes were shown to be associated with RM 8 . Our laboratory had also conducted relevant researches by investigating the association between TOX3(rs3803662) and RM, but there was no significant correlation discoverd 10 . Inspiringly, other researches have found that some polymorphisms related to susceptibility of breast cancer are also participated in occurrence of RM 11‐13 .…”
Section: Introductionmentioning
confidence: 88%
“… 8 Our laboratory had also conducted relevant researches by investigating the association between TOX3(rs3803662) and RM, but there was no significant correlation discoverd. 10 Inspiringly, other researches have found that some polymorphisms related to susceptibility of breast cancer are also participated in occurrence of RM. 11 , 12 , 13 Soon after, another results we conducted 14 have noticed the polymorphism of LncRNA HULC was associated with susceptibility of recurrent spontaneous abortion, which is also associated with the promotion of breast cancer.…”
Section: Introductionmentioning
confidence: 99%